2012
DOI: 10.1111/j.1461-0248.2012.01854.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of plant evolutionary lineages promotes arthropod diversity

Abstract: Large-scale habitat destruction and climate change result in the non-random loss of evolutionary lineages, reducing the amount of evolutionary history represented in ecological communities. Yet, we have limited understanding of the consequences of evolutionary history on the structure of food webs and the services provided by biological communities. Drawing on 11 years of data from a long-term plant diversity experiment, we show that evolutionary history of plant communities - measured as phylogenetic diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
126
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(135 citation statements)
references
References 52 publications
4
126
1
1
Order By: Relevance
“…Nevertheless, we show that bottom-up effects of MPD can prevail to, and influence interactions in, high trophic levels, which has until now only been shown for structurally simple experimental ecosystems (e.g. [26,47]) but not for heterogeneous and species-rich natural forests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, we show that bottom-up effects of MPD can prevail to, and influence interactions in, high trophic levels, which has until now only been shown for structurally simple experimental ecosystems (e.g. [26,47]) but not for heterogeneous and species-rich natural forests.…”
Section: Discussionmentioning
confidence: 99%
“…food for hosts, hosts of parasitoids; see below) and shelter [4]. While for systems with phytophagous hosts, plant MPD directly relates to food availability and diversity [21,26], it is less intuitive how MPD might influence systems with hosts from higher trophic levels. Host-parasitoid interactions in tropical forests are sensitive to microclimate [48], but the cause is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, recent studies have manipulated plant species phylogenetic diversity [29,30], and a metaanalysis by Castagneyrol et al [31 ] reported that mixing closely related tree species increased the susceptibility of focal species to damage by generalist insect herbivores (see also [32] for phylogenetic diversity effects on plant performance). However, it is important to note that effects of phylogenetic diversity would be expected only when there is a strong phylogenetic signal in plant traits, and this is not always the case.…”
Section: The Predictive Role Of Producer and Consumer Traits Plant Trmentioning
confidence: 99%
“…However, the simple assumption that the more time that has passed since two species shared a common ancestor, the higher the probability they have ecologically diverged appears to provide a powerful explanation for how biodiversity affects ecosystem function (15,(18)(19)(20). Previous analyses of the relationship between plant evolutionary history and biomass production used existing experiments that manipulated species richness.…”
mentioning
confidence: 99%